A Family with Epilepsy and Dyskinesia due to Homozygous PRRT2 Gene Mutation - Eshrif, Seham; Adofani, Abdlslam (Ibnosina Journal of Medicine and Biomedical Sciences, 2025)
Proline-rich transmembrane protein 2 (PRRT2) plays an important role in the central nervous system, and mutations in the gene are implicated in various neurological disorders. Variants in PRRT2 (OMIM*614386) can manifest as a variety of clinical phenotypes, including convulsions with paroxysmal choreoathetosis, paroxysmal kinesigenic dyskinesia (PKD), benign familial infantile seizure, and hemiplegic migraine. Here, we report a family with a homozygous PRRT2 variant with benign familial infantile epilepsy and PKD attacks, summarize the clinical characteristics of neurological diseases related to the PRRT2 gene, and explore the therapeutic effects and urge that these patients be treated with acetazolamide during the dyskinesia attacks.
Keywords: proline-rich transmembrane protein 2; benign familial infantile epilepsy; paroxysmal kinesigenic dyskinesia; self-limited infantile epilepsy; antiseizure medication